2019
DOI: 10.1016/j.athoracsur.2018.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Echocardiographic Index of Left Ventricular Filling Pressure in Cardiac Surgery

Abstract: Background. The elevated preoperative ratio of early transmitral flow velocity to early diastolic velocity of the mitral annulus (E/e 0 ) as an echocardiographic index of left ventricular filling pressure is known to be associated with poor postoperative outcomes. We investigated the association between preoperative and postoperative E/e 0 elevation and clinical outcomes after cardiac operations.Methods. The study divided 1,353 patients who underwent cardiac operations into four groups: preoperative and postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…[28][29][30] In those undergoing aortic valve replacement, both pre-and post-operative E/e' have been shown to be associated with post-operative morbidity, including heart failure and acute kidney injury (AKI), and mortality. 1,6,7 This study is the first, to our knowledge, in the pediatric literature to describe the changes in tissue Doppler measurements in the setting of congenital aortic valve surgery and to assess the association with early post-operative outcomes. Eidem et al previously showed that children with unrepaired AS have significantly increased medial and lateral E/e' ratios when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…[28][29][30] In those undergoing aortic valve replacement, both pre-and post-operative E/e' have been shown to be associated with post-operative morbidity, including heart failure and acute kidney injury (AKI), and mortality. 1,6,7 This study is the first, to our knowledge, in the pediatric literature to describe the changes in tissue Doppler measurements in the setting of congenital aortic valve surgery and to assess the association with early post-operative outcomes. Eidem et al previously showed that children with unrepaired AS have significantly increased medial and lateral E/e' ratios when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“… 28 , 29 , 30 In those undergoing aortic valve replacement, both pre‐and post‐operative E/e’ have been shown to be associated with post‐operative morbidity, including heart failure and acute kidney injury (AKI), and mortality. 1 , 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The moderate association between postoperative E/e' values and LCOS in the present study is in agreement with the prognostic value described in larger cohorts. 42 The low observed value of LV longitudinal Doppler parameters may be explained by individual variability associated with sex and age in healthy populations 30 and surgical series. 43 Low increases in lactate concentration have been linked to greater mortality in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%